Correlation of neonatal cord blood with corresponding maternal blood levels of vitamin D3 at birth-a prospective observational study - Jain, Mahavir; Kulkarni, Abhishek; Verma, Rahul; Monteiro, Joewin (International Journal of Contemporary Pediatrics, 2025)
Background: Vitamin D has a pivotal role in bone metabolism and the functioning of the body’s immune, respiratory, endocrine, and cardiovascular systems. Synthesis of vitamin forms the major part of vitamin D stores in the body while dietary sources contribute to a much lesser extent. Vitamin D deficiency in infancy can lead to soft, malformed bones (rickets), seizures due to low blood calcium, and respiratory difficulties. Pregnant women and children are considered a high-risk group for vitamin D deficiency. The level of 25 (OH) D in neonates at birth depend entirely on their mothers’ levels and several studies have shown a correlation between cord blood 25(OH)D levels and those of their mothers. We designed an observational study to assess the correlation between cord blood 25 (OH) D levels of the neonate at birth and the corresponding maternal blood 25 (OH) D levels. Methods: A prospective observational study was conducted between June 2022 to June 2023 at the in-patient department of Sir HN Reliance Foundation Hospital and Research Centre, with prior institutional ethical clearance. A cohort consisting of mother-baby dyads, where the baby was a full term, healthy, singleton of either gender, irrespective of the mode of delivery was studied. Residual cord blood serum, taken for routine testing, was collected for study. Maternal serum procured routinely before deliveries for serology studies was used for estimation of 25 (OH) D levels. Results: A total of 54 dyads of mother-baby were enrolled during the study period. 15 (27.78 percent) mothers had insufficient vitamin D levels, 6 (11.11 percent) were vitamin D deficient and 33 (61.11 percent) had sufficient vitamin D levels. The mean 25 (OH) D level among newborns was 26.37 (±10.92) ng/ml. 19 (35.19 percent) newborns had insufficient vitamin D levels, whereas 17 (31.48 percent) were vitamin D deficient. There was a significant correlation observed between maternal and newborn vitamin D status (p=0.013). Conclusion: A significant correlation was observed between the vitamin D levels of mothers and their neonates at birth, highlighting the crucial role of maternal vitamin D levels. Since fetuses rely entirely on their mothers for vitamin D, it is essential to ensure that antenatal vitamin D levels in pregnant woman are sufficient.